Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jamanetworkopen.2021.22044
|View full text |Cite
|
Sign up to set email alerts
|

Home Hazard Removal to Reduce Falls Among Community-Dwelling Older Adults

Abstract: IMPORTANCE Falls are the leading preventable cause of morbidity, mortality, and premature institutionalization for community-dwelling older adults.OBJECTIVE To test the effectiveness of a behavioral intervention on fall risk among older adults receiving services from an Area Agency on Aging. DESIGN, SETTING, AND PARTICIPANTSThis randomized clinical trial examined a home hazard removal intervention in the community using a race-and sex-stratified randomization design. Older adults receiving services from the Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…The greatest reductions are seen when the intervention is delivered to those at highest risk of falling [ 77 , 124 , 127 , 174 , 175 ].…”
Section: Management and Interventionsmentioning
confidence: 99%
“…The greatest reductions are seen when the intervention is delivered to those at highest risk of falling [ 77 , 124 , 127 , 174 , 175 ].…”
Section: Management and Interventionsmentioning
confidence: 99%
“…In a randomized clinical trial, Stark and colleagues found that removal of home hazards and tailored self-management strategies decreased fall rate among older adults at risk for falls. There were no differences in time to first fall or other prespecified outcomes of daily activity performance, falls efficacy, or self-reported quality of life.…”
mentioning
confidence: 99%
“…Other multicomponent fall programs have used a person- and purpose-directed approach to setting goals with the expertise of an occupational therapist, nurse, and maintenance and repair professional to intervene on the person and their lived environment, resulting in reduced disability and increased falls efficacy . The study by Stark et al adds to this body of evidence that intervening with the home and the person could be an important strategy and the actual provision of services seems to have a stronger impact on falls than referral alone for services.…”
mentioning
confidence: 99%
See 2 more Smart Citations